Global Research Trends in Environmental Education and Environmental Awareness: A Bibliometric Analysis - Jesús Enrique Quezada Castro; María del Pilar Quezada Castro (Jurnal Pendidikan IPA Indonesia, 2026)
Environmental education and awareness are recognized as strategic pillars of sustainable development for addressing the challenges posed by the global ecological crisis. However, scientific output has become fragmented, hindering the identification of emerging trends and research gaps. The objective of this study was to analyses the evolution of scientific output published between 1999 and 2024 using bibliometric analysis. The study followed the PRISMA guidelines to ensure transparency and reproducibility of results. Inclusion and exclusion criteria were applied, and a total of 820 documents were analyzed. VOSviewer and Biblioshiny were used to map the selected publications. The results showed that the annual growth rate of scientific output was 13.38%, evidence of the progressive consolidation of the field of research. Journals ranked in the first and second quartiles of Scopus stood out for the number of publications related to the study topic. China and the United Kingdom emerged as leaders in international collaboration and citation impact, evidence of the consolidation of global research networks. The thematic analysis indicates that the main pillars of the research focus on environmental education, pro-environmental behavior, and environmental awareness, which are consolidated through educational practices grounded in sustainability. It was concluded that, since 2012, researchers' interest in the topic has increased significantly, contributing to the systematization of scientific knowledge and identifying future lines of research, particularly on environmental awareness and its impact on early childhood education.